A General Route Towards Defect and Pore Engineering in Graphene. Issue 11 (7th March 2014) - Xie, Guibai; Yang, Rong; Chen, Peng; Zhang, Jing; Tian, Xuezeng; Wu, Shuang; Zhao, Jing; Cheng, Meng; Yang, Wei; Wang, Duoming; He, Congli; Bai, Xuedong; et al.
<x xml:space="preserve">Abstract</x> Defect engineering in graphene is important for tailoring graphene's properties thus applicable in various applications such as porous membranes and ultra‐capacitors. In this paper, we report a general route towards defect‐ and pore‐ engineering in graphene through remote plasma treatments. Oxygen plasma irradiation was employed to create homogenous defects in graphene with controllable density from a few to ≈103 (μm−2). The created defects can be further enlarged into nanopores by hydrogen plasma anisotropic etching with well‐defined pore size of a few nm or above. The achieved smallest nanopores are ≈2 nm in size, showing the potential for ultra‐small graphene nanopores fabrication.